Relationship of Genotype, Phenotype, and Treatment in Dopa‐Responsive Dystonia: MDSGene Review - Anne Weißbach; Martje G. Pauly; Rebecca Herzog; Lisa Hahn; Sara Halmans; Feline Hamami; Christina Bolte; Sarah Camargos; Beomseok Jeon; Manju A. Kurian; Thomas Opladen; Norbert Brüggemann; et al. (2021)
Abstract Background Pathogenic variants in 5 genes ( GCH1 , TH , PTS , SPR , and QDPR ), involved in dopamine/tetrahydrobiopterin biosynthesis or recycling, have been linked to Dopa‐responsive dystonia (DRD). Diagnosis and treatment are often delayed due to high between‐ and within‐group variability. Objectives Comprehensively analyzed individual genotype, phenotype, treatment response, and biochemistry information. Methods 734 DRD patients and 151 asymptomatic GCH1 mutation carriers were included using an MDSGene systematic literature review and an automated classification approach to distinguish between different forms of monogenic DRDs. Results Whereas dystonia, L ‐Dopa responsiveness, early age at onset, and diurnal fluctuations were identified as red flags, parkinsonism without dystonia was rarely reported (11%) and combined with dystonia in only 18% of patients. While sex was equally distributed in autosomal recessive DRD, there was female predominance in autosomal dominant DYT/PARK‐ GCH1 patients accompanied by a lower median age at onset and more dystonia in females compared to males. Accordingly, the majority of asymptomatic heterozygous GCH1 mutation carriers (>8 years of age) were males. Multiple other subgroup‐specific characteristics were identified, showing high accuracy in the automated classification approach: Seizures and microcephaly were mostly seen in DYT/PARK‐ PTS , autonomic symptoms appeared commonly in DYT/PARK‐ TH and DYT/PARK‐ PTS , and sleep disorders and oculogyric crises in DYT/PARK‐ SPR . Biochemically, homovanillic acid and 5‐hydroxyindoleacetic acid in CSF were reduced in most DRDs, but neopterin and biopterin were increased only in DYT/PARK‐ PTS and DYT/PARK‐ SPR . Hyperphenylalaninemia was seen in DYT/PARK‐ PTS , DYT/PARK‐ QDPR , and rarely reported in autosomal recessive DYT/PARK‐ GCH1 . Conclusions Our indicators will help to specify diagnosis and accelerate start of treatment. © 2021 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society